RELIGION A FUNDAMENTAL ELEMENT IN THE SOCIETAL ANALYSIS OF KARL MARX AND MAX WEBER: A COMPARATIVE STUDY - Silva, Willie R. de (Journal of Dharma, 1987)
It is atruism to say that the present western society - its institutions and ideas-is based on concepts coming basically from tbe previous century;' it could be no less true of social sciences. Giddens, who "conceived tbe project of examining the residue of nineteenth century European social theory for contemporary problems in the social sciences" (Giddens 1979: 294),* observes: "It ... still seems to me now, that social science in the contem- porary world bears the strong imprint of ideas worked out in the nineteenth and early twentieth centuries in Europe" (Giddens 1979: 1).